1998
DOI: 10.1103/physrevd.57.3503
|View full text |Cite
|
Sign up to set email alerts
|

Upper bound for entropy in asymptotically de Sitter space-time

Abstract: We investigate nature of asymptotically de Sitter space-times containing a black hole. We show that if the matter fields satisfy the dominant energy condition and the cosmic censorship holds in the considering space-time, the area of the cosmological event horizon for an observer approaching a future timelike infinity does not decrease, i.e. the second law is satisfied. We also show under the same conditions that the total area of the black hole and the cosmological event horizon, a quarter of which is the tot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…In Ref. [17], the authors have shown that the final values of entropies of the event (S B ) and cosmological (S C ) horizon satisfy the inequality…”
Section: Entropy Of Sdsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [17], the authors have shown that the final values of entropies of the event (S B ) and cosmological (S C ) horizon satisfy the inequality…”
Section: Entropy Of Sdsmentioning
confidence: 99%
“…A naive extension of these approaches to SdS leads us to the conclusions that the SdS has two different temperatures associated with the two horizons. Using this extension, it has been argued [6,17] that the SdS will inevitably evolve towards an empty de Sitter space indicating that SdS may never be in thermodynamic equilibrium with a single temperature associated with the space-time.…”
Section: Introductionmentioning
confidence: 99%
“…on the BEH, while we leave U unchanged. Since the area of the BEH is non-decreasing and also has an upper bound as shown in [13,14], lim v→∞ R = C 3 , and R ,v ∼ C 4 v −β−1 (β > 0). This means that by Eq.…”
mentioning
confidence: 99%
“…First, we will consider the asymptotic behavior of field functions near the cosmological event horizon (CEH), which is defined as a past Cauchy horizon H − (I + ) when a BEH exists (see Ref. [14]). It is convenient to rescale the coordinate U such that U is an affine parameter of a null geodesic of the CEH, i.e., λ is constant along the CEH.…”
mentioning
confidence: 99%
See 1 more Smart Citation